2021
DOI: 10.1111/odi.13878
|View full text |Cite
|
Sign up to set email alerts
|

SNHG1/miR‐186/FUT8 regulates cell migration and invasion in oral squamous cell carcinoma

Abstract: Recently, lncRNAs are associated with the progression and development of various cancers. We aimed to explore the effects of lncRNA SNHG1 on the proliferation, apoptosis, migration, and invasion of oral squamous cell carcinoma (OSCC) cells. Quantitative real-time PCR (RT-qPCR) was used for measurement of SNHG1 in OSCC cells. Cell proliferation, apoptosis, migration, and invasion were detected by CCK-8 assay, flow cytometry, Cell Death Detection ELISA PLUS kit, and transwell assays. Dual-luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recently, a transcriptome investigation revealed that long non-coding RNAs (lncRNAs) are putative players in the tumorigenesis of most tumors [ 4 ]. LncRNA SNHG1 expression levels are elevated in OSCC cells and promote tumor cell growth by downregulating the expression of fucosyltransferase 8 by targeting microRNA (miR)-186 [ 5 ]. MYC-induced lncRNA enhances the invasion of OSCC cells by modulating the Wnt/β-catenin pathway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a transcriptome investigation revealed that long non-coding RNAs (lncRNAs) are putative players in the tumorigenesis of most tumors [ 4 ]. LncRNA SNHG1 expression levels are elevated in OSCC cells and promote tumor cell growth by downregulating the expression of fucosyltransferase 8 by targeting microRNA (miR)-186 [ 5 ]. MYC-induced lncRNA enhances the invasion of OSCC cells by modulating the Wnt/β-catenin pathway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the anticancer roles of miR‐186‐5p were observed in gastric cancer, 25 colorectal cancer, 26 and ovarian cancer. 27 In OSCC, multiple studies found miR‐186 was a tumor suppressor in OSCC by targeting FUT8 28 and SHP2. 29 Here, we for the first time proved that miR‐186‐5p was proved to be downregulated in OSCC samples, and FNDC3B was a target of miR‐186‐5p in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In oral squamous cell carcinoma (OSCC), miR-186 has been discovered to directly target and inhibit the expression of FUT8. Nevertheless, a highly expressed lncRNA SNHG1 functions as a sponge for miR-186, counteracting its inhibitory effect and promoting the malignant growth of OSCC [102]. And miR-198 has been found to act directly on the 3 ′ UTR of FUT8 in CRC, thereby reducing FUT8 expression and inhibiting cell proliferation, migration, and invasion [100].…”
Section: At the Post-transcriptional Levelmentioning
confidence: 99%